Training and Updating of Education Boards in Indigenous Schools of Rural Areas: Strengthening Local Education Management - Nancy Torres-Victoria; Oscar Castro-Vargas (Revista Electrónica Educare)
Education management in the schools of indigenous rural areas faces a number of difficulties to implement and comply with the guidelines and requirements of the laws related to budgetary management of resources allocated to Education or Administrative Boards. In addition to being located in scattered rural areas, far from the municipal heads and regional offices of the Ministry of Public Education, one of the main obstacles is that all regulations, laws and guidelines are written in Spanish, and there is people, in this indigenous rural communities, who do not speak, write, read or understand this language. This puts them at an enormous disadvantage, which has a direct impact on the indigenous children’s right to education.